Correlation Between Oral Lichen Planus and Thyroid Disease in China: A Case–Control Study - Zhou, Tingting; Li, Dan; Chen, Qianming; Hua, Hong; Li, Chunlei (Frontiers in Endocrinology, 2018)
Background: A possible relationship between oral lichen planus (OLP) and thyroid disease has received attention in recent years. Objective: This study aimed to evaluate the correlation between OLP and thyroid diseases in Chinese ethnic patients. Methods: 192 OLP patients, 123 patients with oral lichenoid lesions (OLL), and 162 controls were recruited in this case-control study. All participants received screening for thyroid function and underwent ultrasound. Sex and age of the patients in the three groups were matched. The prevalence of thyroid diseases in the subjects was analyzed. Using logistic regression, the odds ratio (OR) with 95% confidence intervals (CI) was appraised for associations between OLP, OLL, and different types of thyroid diseases (Hashimoto’s Thyroiditis（HT）, hypothyroidism, and thyroid nodule). Results: The prevalence of thyroid diseases in the OLP group (72.4%) and OLL group (68.3%) was higher than the control group (49.4%) with statistical significance. The OR of HT was 3.16 (1.87-5.33) for OLP, 2.09 (1.18-3.70) for OLL, while the OR of thyroid nodule was 2.31 (1.30-4.09) for OLP. Conclusion: Our study suggested a close relationship between OLP/OLL and HT and thyroid nodule in a Chinese population. The possible mechanism behind this association warrants further investigation.